2004
DOI: 10.2105/ajph.94.10.1695
|View full text |Cite
|
Sign up to set email alerts
|

Person and Place: The Compounding Effects of Race/Ethnicity and Rurality on Health

Abstract: Rural racial/ethnic minorities constitute a forgotten population. The limited research addressing rural Black, Hispanic, and American Indian/Alaska Native populations suggests that disparities in health and in health care access found among rural racial/ethnic minority populations are generally more severe than those among urban racial/ethnic minorities. We suggest that disparities must be understood as both collective and contextual phenomena. Rural racial/ethnic minority disparities in part stem from the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
266
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(277 citation statements)
references
References 75 publications
8
266
0
3
Order By: Relevance
“…This limitation is important because although many rural counties are predominantly non-Hispanic white, high numbers of African American, Hispanic, and Native American populations are geographically concentrated in several rural regions, often where health care disparities are the most acute. [36][37][38] Finally, the study results may be influenced by our interpretation as researchers; we sought to minimize this bias by engaging in a continuous process of reflexivity.To read or post commentaries in response to this article, see it online at http://www.annfammed.org/content/14/3/244. …”
mentioning
confidence: 99%
“…This limitation is important because although many rural counties are predominantly non-Hispanic white, high numbers of African American, Hispanic, and Native American populations are geographically concentrated in several rural regions, often where health care disparities are the most acute. [36][37][38] Finally, the study results may be influenced by our interpretation as researchers; we sought to minimize this bias by engaging in a continuous process of reflexivity.To read or post commentaries in response to this article, see it online at http://www.annfammed.org/content/14/3/244. …”
mentioning
confidence: 99%
“…The third measure, the rate of serious complications due to perforation, is historically predicted to be between 1 per 500 and 1 per 1000. 34 Fortunately, though, these primary care physicians have experienced only one fourth of this rate. Admittedly, the primary care physicians screen their healthy asymptomatic patients and continue to refer those patients who pose higher risks or require diagnostic evaluation of symptoms.…”
Section: Primary Care Physician Trainingmentioning
confidence: 99%
“…There is strong evidence that asthma has a higher prevalence in rural populations [1,3,11]. Furthermore, Probst, et al (2004) reported that health disparities among rural minority populations were more severe than among urban minorities for a number of health-related conditions [12].…”
Section: Introductionmentioning
confidence: 99%